TIC como mediación didáctica para el fortalecimiento de la convivencia escolar en los estudiantes del grado quinto (2019)
The purpose of this research work is to analyze the effects of ICT as a didactic mediation in strengthening the coexistence of fifth grade students at the Agricultural Technical Institution of Suarez in the Municipality of Suarez Cauca-Colombia. We worked under the complementary paradigm with a mixed approach of descriptive-explanatory type. To this end, a diagnostic questionnaire was applied to identify the state of school coexistence in a sample of 60 fifth-grade students, which were intentionally selected, as well as a group of 6 selected teachers from a population of 6 12 teachers from the primary school of the Technical Institution of Suarez, subsequently, were identified and applied during an academic period didactic strategies with the use of ICT in order to strengthen the school coexistence of the students selected for the project, and finally, It determined the effects that the strategies mediated by the TIC had on the school coexistence in the students. The study showed that students strengthened interpersonal relationships by improving coexistence with others, likewise, it was evidenced that (70%) of students were motivated to work in a learning environment mediated by ICT, considering it as an effective tool for the strengthening of healthy coexistence. It was concluded that the implementation of ICT was significant because it made it easier for teachers to promote a more harmonious environment in the classroom by reducing the problem of school violence, which facilitated the recognition of standards, respect for others, tolerance, and the implementation of healthy coexistence.